Urban Transportation and the Environment: Issues, Alternatives and Policy Analysis - Yedla, Sudhakar (Springer, 2015)
The book deals with urban transportation planning in light of environmental sustainability and social equity. It begins with a review of the Indian urban transportation system and the issues surrounding it, and discusses the alternatives and policy directions that are being considered. It examines all the environmental issues arising out of transportation as a sector and assesses the alternatives that can be considered to improve sustainability. Further, the book not only analyses transportation modes that cater to the travel needs of the poor, so as to make them more socially equitable, but also explores measures to promote them using a multi-criteria and multi-stakeholder approach. It addresses the barriers that are bottlenecks for the implementation of cleaner fuels and modes of transport and presents an incremental approach to tackle environmental concerns, including climate change, when planning transportation in the long term. Finally, it presents the dilemma of city administrators in choosing between strategies aimed at local pollution control and those aimed at limiting global emissions. This unique book provides a comprehensive overview of “sustainable transportation.” It discusses all the important elements that are essential to transportation planners and policy makers when planning a city’s transportation. Theoretical presentations augmented by case-specific research work and the methodology used in some of the modules, make it a valuable resource for researchers working at the forefront of this area.